Evaluation of The Program For The Fulfillment of The Rights of Victims of Human Rights Violations in Indonesia - Mugiyanto, Mugiyanto; Mustofa, Amirul; Ferriswara, Dian (Socious Journal, 2025)
The Victim Recovery and Prevention of Gross Human Rights Violations Program (PKPHAM) is a policy of the Indonesian government launched to respond to the demands for justice for victims of gross human rights violations in the past, as well as to strengthen national reconciliation based on justice and humanity. This study aims to evaluate the results of the implementation and monitoring of the PKPHAM program through a qualitative approach using William N. Dunn's public policy evaluation theory which includes six main indicators: (1) Effectiveness, (2) Efficiency, (3) Adequacy, (4) Equity, (5) Responsiveness, and (6) Accuracy. The findings of this study show that the implementation of the program still faces a number of obstacles, including; limited validated victim data, lack of coordination between implementing agencies, and there are several forms of assistance that are not suitable for the concrete needs of victims. On the monitoring side, the approach used is still administrative, with no clear impact indicators and adequate victim participation. Evaluations show that most programs are still symbolic and have not substantially fulfilled the victims' rights to truth, justice, reparation, and guarantees of non-recurrence. Thus, in order for PKPHAM to become an effective and sustainable program, fundamental improvements are needed in the design and implementation of policies that are oriented towards the fulfillment of victims' rights as a whole. The state needs to strengthen political commitments, improve the victim-based monitoring system, and adopt a participatory, accountable, and fair approach in realizing transitional justice in Indonesia.